O arquivo pessoal do teatrólogo Augusto Boal: o espetáculo continua - França, Patrícia Machado Goulart (2015)
This research presents the archival history of the personal archive of the playwright Augusto Boal, highlighting the places in which the acquis was to get to your destination. Highlights public investments channeled to the collection in question, as the purpose of founding a Inter-University Centre of Memory and Documentation (CIM). It also discusses considerations related to the organization of personal files, stressing the importance of the treatment is guided by principles and methods of printing. In addition, the research describes the procedures applied in the systematic, ongoing, this personal collection, suggesting an alternative model of organization, with the aim of contributing to their access and dissemination.